Successful Treatment of Extensively Drug-Resistant Acinetobacter baumannii Intracranial Infection with Meropenem and Cefoperazone Sodium Sulbactam: A Case Report - Ma W; Zhang C; He B; Lv X; Luo P (Infection and Drug Resistance)
Wenke Ma,1 Chao Zhang,1 Bei He,1 Xinwen Lv,1 Peng Luo2 1Department of Neurosurgery, Baoji Central Hospital, Baoji, Shaanxi, People’s Republic of China; 2Department of Neurosurgery, The First Affiliated Hospital of Air Force Medical University, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Xinwen Lv, Department of Neurosurgery, Baoji Central Hospital, Baoji, Shaanxi, 721008, People’s Republic of China, Email lvxinwen.2008@163.com Peng Luo, Department of Neurosurgery, The First Affiliated Hospital of Air Force Medical University, Xi’an, Shaanxi, 710032, People’s Republic of China, Email lpmail_19@126.comBackground: Acinetobacter baumannii intracranial infections, especially those caused by multidrug-resistant (MDR) or extensively drug-resistant (XDR) strains, have posed an increasing challenge to treatment because of poor drug permeability through the blood–brain barrier (BBB) and increased bacterial drug resistance. Therefore, we aimed to explore a therapeutic schedule for Acinetobacter baumannii intracranial infection.Case Presentation: We reported a case of intracranial infection caused by XDR A. baumannii after severe traumatic brain injury, cerebrospinal fluid (CSF) rhinorrhea, and severe pneumonia that was successfully treated with meropenem and cefoperazone sodium sulbactam.Conclusion: This case illustrated that meropenem combined with cefoperazone sodium sulbactam could still be a therapeutic option against intracranial XDR A. baumannii infection.Keywords: intracranial infection, Acinetobacter baumannii, extensively drug-resistant, meropenem, cefoperazone sodium sulbactam